2015
DOI: 10.1039/c5gc00006h
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of isatins with 6-amino uracils and isoxazoles: isatin ring-opening vs. annulations and regioselective synthesis of isoxazole fused quinoline scaffolds in water

Abstract: A straightforward approach for the one-pot synthesis of isoxazoloquinoline and spiroxindole derivatives in water has been established using p-toluene sulphonic acid as a catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…The formation of spirooxindoles was found to be favored only when Nalkyl/aryl/benzyl-substituted isatins were used otherwise the side product isoxazoloquinolines were obtained predominantly (Scheme 9). 27 Novel spiro[oxindole-isoxazolidine] derivatives have been synthesized via 1,3-dipolar cycloaddition reactions of variously substituted maleimides with isatin ketonitrone (Scheme 10). The reactants, substituted maleimides, were prepared separately using maleic anhydride and aniline, whereas isatin ketonitrone was prepared via multiple steps using isatin, aniline, and phenyl hydroxylamine.…”
Section: Spiro Derivativesmentioning
confidence: 99%
“…The formation of spirooxindoles was found to be favored only when Nalkyl/aryl/benzyl-substituted isatins were used otherwise the side product isoxazoloquinolines were obtained predominantly (Scheme 9). 27 Novel spiro[oxindole-isoxazolidine] derivatives have been synthesized via 1,3-dipolar cycloaddition reactions of variously substituted maleimides with isatin ketonitrone (Scheme 10). The reactants, substituted maleimides, were prepared separately using maleic anhydride and aniline, whereas isatin ketonitrone was prepared via multiple steps using isatin, aniline, and phenyl hydroxylamine.…”
Section: Spiro Derivativesmentioning
confidence: 99%
“…Abd El-Fatah et al [139] developed a series of bis(tetrahydro [1,2,4] [140] reported that the reaction of isatin 5, Table 17). [141,142] One-pot, three-components reactions of indandione 122, isatin 5, and enamine 12 in the presense of L-proline as a catalyst in 2-propanol at reflux afforded spiro(ideno [1,2-b]pyridine-indoline) derivatives 124 in good yields (Scheme 68).…”
Section: [124]triazolo[51-b]quinazolinesmentioning
confidence: 99%
“…Perumal et al . achieved multi‐substituted quinolines through a Pfitzinger reaction in the presence of a catalytic amount of p ‐toluenesulfonic acid (Scheme ).…”
Section: Synthesis Routes To Functionalized Quinolinesmentioning
confidence: 99%
“…Perumale tal. [36] achieved multi-substituted quinolines through aP fitzinger reactioni nt he presenceo fac atalytic amount of p-toluenesulfonic acid (Scheme20). Isatin, 6-aminouracil and isoxazole undergo Aldol addition, ring opening, ring closure, ring contractiona nd aromatization to give the final quinoline products in excellent yield.…”
Section: Synthesesf Rom Other Materialsmentioning
confidence: 99%